EFISIENSI BIAYA DAN PERBEDAAN PENDAPATAN AGROINDUSTRI TEMPE SEBELUM DAN SESUDAH KENAIKAN HARGA BAHAN BAKAR MINYAK (BBM) - Sudarko Sudarko (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2007)
This research aim were to know; (a) the influencing factors of production of tempe; (b) The cost efficiency of  tempe production; and (c) The income of tempe enterpreneur; pass the increase of oil price. The research location selected by purposive method, in Baratan Kecil Village, Patrang Subdistrict in Jember Regency. Research methods that used were descriptive, correlational, analitic, and comparative. Population and sample determined by simple random sampling. Data that used in this research both primary and secondary. The methods used to analyze the data were; (a) Cobb-Douglas Production function; (b) t-paired test.; and (c) Income and cost Analyzes. Result shows that; (1) soybean, labours, ragi, and wood of agroindustry definitely infhered to tempe production in significantly level confidence degree. Furthermore oil price and condition of the oil price indefinitely of tempe in degree of confidence 95%; (2) The production cost of  tempe is efficien, (3) The income of the enterpreneur either before and after the increasing of oil  is significantly different at significantcy  level 5%. Keywords: Production factor of tempe agroindustry, cost efficiency, income of  tempe enterpreneur